2011
DOI: 10.1186/1472-6963-11-111
|View full text |Cite
|
Sign up to set email alerts
|

What causes treatment failure - the patient, primary care, secondary care or inadequate interaction in the health services?

Abstract: BackgroundOptimal treatment gives complete relief of symptoms of many disorders. But even if such treatment is available, some patients have persisting complaints. One disorder, from which the patients should achieve complete relief of symptoms with medical or surgical treatment, is gastroesophageal reflux disease (GERD). Despite the fact that such treatment is cheap, safe and easily available; some patients have persistent complaints after contact with the health services. This study evaluates the causes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…For example, none of the physicians involved in this patient experience asked IG about his occupation, suggesting inadequacy in history taking. In a Norwegian study assessing failure of treatment of GERD, it was reported that failure of interaction of physicians between different levels of healthcare was a leading contributor in treatment failure . This was similar to what was observed in this patient experience where there was no interaction between physicians even between physicians in the same hospital.…”
Section: Discussionsupporting
confidence: 82%
“…For example, none of the physicians involved in this patient experience asked IG about his occupation, suggesting inadequacy in history taking. In a Norwegian study assessing failure of treatment of GERD, it was reported that failure of interaction of physicians between different levels of healthcare was a leading contributor in treatment failure . This was similar to what was observed in this patient experience where there was no interaction between physicians even between physicians in the same hospital.…”
Section: Discussionsupporting
confidence: 82%
“…The design of the intervention also increased the interchange between the hospital and the primary care physicians. Lack of such communication is often pointed out as a problem . This approach also reduced the risk of conflicting messages to the participants regarding their drug treatment because only the responsible physician discussed the drug treatment with the participant.…”
Section: Discussionmentioning
confidence: 99%
“…All participants’ perceptions of care integration will be captured in the exit questionnaire. In the absence of a formally validated instrument to measure the outcome of interest [70], the measurement tool will consist of a customized version of a questionnaire on the perception of care integration from a patient perspective [71]. Five questions, corresponding to the interaction subscale, are being used to investigate this study objective on program integration.…”
Section: Methodsmentioning
confidence: 99%